Comparison of Oxacillin Disc Diffusion Test with mecA Polymerase Chain Reaction and Cefoxitin Disc Diffusion Test for the Detection of Oxacillin-resistant Staphylococcus aureus Collected from Baghdad Hospitals - Al-Ugaili, Dhafar; Fadhil, A-M A; Wohaieb, Saleh A (Al-Nahrain Journal of Science, 2018)
This study was carried out to evaluate the accuracy of oxacillin and cefoxitin disc diffusion testcompared with mecA gene-positive PCR isolates. Two hundred and six clinical swabs fromnose, hand and ear were collected from four different hospitals in Baghdad. The diagnostic results showed that (154) out of (206) samples gave positive bacterial culture, (61) of them were confirmed as Staphylococcusaureus; of which 47 (77%) were oxacillin-resistant Staphylococcus aureus and exhibited multiple resistances to other tested antibiotics. Depending on the MICs values;23 isolates was chosen. Plasmid profiles revealed that (11) out of (23) had a plasmid with different molecular weight. Using polymerase chain reaction assay, 19 isolates were found to havemecA geneand results of agarose gel revealed the presence of DNA band at (200 bp.); the results detect a correlation between the positivity of the isolates for cefoxitin resistant test and the molecular study for the presence of (mecA).